Theoretical and Numerical Analyses of Steel-timber Composite Beams with LVL Slabs - Strzelecka, Julia; Polus, Łukasz; Chybiński, Marcin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Recently conducted studies have shown that significant benefits are to be gained by joining steel beams and timber slabs. Steel-timber composite beams present a sustainable solution for the construction industry because of their high strength and stiffness, and lower carbon footprint and self-weight than steel-concrete composite beams.
Keywords: steel-timber composite beams; laminated veneer lumber (LVL); Finite Element Method (FEM)